Arte Italiana 1945-1995 : Il visibile e l'invisibile. - Museum of Contemporary Art, Tokyo; Yonago City Museum of Art, Tottori; Hiroshima City Museum of Contemporary Art, Hiroshima; Corà, Bruno; Haito, Masahiko; Nanjo, Fumio; Oda, Runa; Puppo, Alessandro Del (Nagoya : Aichi Prefectural Museum of Art, 1997)
Anselmo, Giovanni ; Bagnoli, Marco ; Bianchi, Domenico ; Boetti, Alighiero ; Burri, Alberto ; Calzolari, Pierpaolo ; Castellani, Enrico ; Colla, Ettore ; Cucchi, Enzo ; de Dominicis, Gino ; Dessi, Gianni ; Fabro, Luciano ; Fontana, Lucio ; Kounellis, Jannis ; Savio, Francesco Lo ; Manzoni, Piero ; Melotti, Fausto ; Merz, Mario ; Paladino, Mimmo ; Paolini, Giulio ; Pascali, Pino ; Penone, Giuseppe ; Pistoletto, Michelangelo ; Salvadori, Remo ; Spalletti, Ettore ; Zorio, Gilberto
biografie
Arte Italiana 1945-1995 : Il visibile e l'invisibile, Aichi Prefectural Museum of Art, Nagoya, November 14th, 1997 - January 15th, 1998 ; Museum of Contemporary Art, Tokyo, February 1st, 1998 - March 22nd, 1998 ; Yonago City Museum of Art, Tottori, April 23rd, 1998 - May 26th, 1998 ; Hiroshima City Museum of Contemporary Art, Hiroshima, June 15th, 1998 - July 26th, 1998
Engels & Italiaans & Japans
boek
Keywords: naoorlogse periode; Italië